Migration, remittances and development: A case study of Senegalese labour migrants on the island Boa Vista, Cape Verde - Jung, Philipp (2015)
Cape Verde has become increasingly a destination for international migrants from continental West Africa. The aim of this paper is to explore migration of Senegalese to the Cape Verdean island of Boa Vista with a focus on migration decisions and remittances and attempts to link it with the broader migration and development debate. It starts with a review of the literature on empirical findings and theoretical approaches examining migration as a method of risk minimization and links between migration and development. In the second part these approaches are reviewed in the light of empirical evidence about migration processes and flows of remittance between Senegal and Cape Verde. The importance of Cape Verde as a destination for international migrants from West Africa has increased considerably since the millennium. This article present data examining the motives for emigration and immigration and the characteristics of the remittances sent by migrants.